Anti-Urolithiatic Effect of Ethanolic Extract of Pedalium Murex Linn. Fruits on Ethylene Glycol-Induced Renal Calculi - Mandavia, Divyesh R.; Patel, Mahendra K.; Patel, Jayshree C.; Anovadiya, Ashish P.; Baxi, Seema N.; Tripathi, Chandrabhanu Rajkishor (Urology Journal, 2013)
Purpose: To evaluate effect of ethanolic extract of Pedalium murex Linn. fruits on experimental model of calcium oxalate nephrolithiasis. Materials and Methods: Thirty-six male Wistar albino rats were randomly divided in 6 groups. Normal controls received distilled water for 28 days. Other five groups received ethylene glycol (1% v/v) in distilled water for 28 days. Pedalium murex ethanolic extract was given 200 mg/kg and 400 mg/kg orally in distilled water for 28 days in prophylactic groups (III and IV) and from 15th to 28th days in treatment groups (V and VI). The urea, creatinine, random blood sugar, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, bilirubin and calcium were measured on 28th day. 24 hr urinary oxalate and volume were measured on day 0 and 28. On day 28, kidneys were removed, weighed and subjected to histopathological examination. Calcium oxalate crystallization was evaluated by renal histopathology and in-vitro method of mineralization. All parameters were analyzed by Kruskal-Wallis or one-way ANOVA with post-hoc test. Results: Pedalium murex showed significant improvement in renal function and kidney weight in prophylactic groups as compared to ethylene glycol controls. It did not show any effect on urinary oxalate, urine volume and any other serological parameters. Calcium oxalate crystallization was significantly reduced in all the Pedalium murex treated groups (P < .05). Calcium oxalate and phosphate mineralization were also inhibited by 33% and 57%. Conclusion: Ethanolic extract of Pedalium murex fruits possess significant activity for prevention of renal calculi.